Vygotsky and special needs education : rethinking support for children and schools - Daniels, Harry; Hedegaard, Mariane (Continuum International Pub. Group, 2011)
After Piaget, Vygotsky is perhaps the most important educational theorist of the twentieth century. Support for schools and pupils with additional needs has been theorised in a number of ways over the last 100 years and much interest has been shown in the development and relevance of Vygotsky's ideas. It is ironic, therefore, that so little has been written about the practical application of such a perspective to the field. This book brings together researchers working in the UK and Denmark to reflect on the benefits to be had from taking such a stance on support for children and schools. All.